REPRESENTASI VIKTIMISASI PEREMPUAN DALAM HUBUNGAN ROMANTIS PADA FILM LIKE & SHARE (2022) - Adrian Budynata, Johan; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The high incidence of dating violence and the higher number of women as victims serve as the background for this research. This study aims to examine how the film